2017
DOI: 10.1021/acs.jnatprod.6b01052
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Privileged Antichlamydial Natural Products by a Ligand-Based Strategy

Abstract: The obligate intracellular pathogen Chlamydia pneumoniae remains a difficult target for antimicrobial therapy. Owing to the permeability barrier placed by bacterial and host vacuolar membranes, as well as the propensity of the bacterium for persistent infections, treatment failures are common. Despite the urgent need for new antichlamydial compounds, their discovery is challenged by the technically demanding assay procedures and lack of validated targets. An alternative strategy of using naturally occurring co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…ChemGPS-NP, a PCA (Principle Component Analysis)-based model applied to natural products, was first developed by the Backlund group in 2007 [ 11 ], and an entire online analysis system that provides the eight principal components (PCs) was further established by the same group in 2009 [ 12 ]. In the last few years, this computational tool has been employed to analyze structure-activity relationships (SAR) [ 13 , 14 ] and to further investigate promising pharmacological targets, guiding natural product drug discovery [ 15 , 16 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…ChemGPS-NP, a PCA (Principle Component Analysis)-based model applied to natural products, was first developed by the Backlund group in 2007 [ 11 ], and an entire online analysis system that provides the eight principal components (PCs) was further established by the same group in 2009 [ 12 ]. In the last few years, this computational tool has been employed to analyze structure-activity relationships (SAR) [ 13 , 14 ] and to further investigate promising pharmacological targets, guiding natural product drug discovery [ 15 , 16 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Also, macrolides' massive use has raised resistance markers among other bacterial species (Bojang et al, 2017;Mohammadzadeh et al, 2019). All this evidence supports the need for constant efforts to continue searching for new antichlamydial agents (Alvesalo et al, 2006;Salin et al, 2010;Yamazaki et al, 2005;Osaka et al, 2012;Kahru et al, 2017;Petyaev et al, 2017).…”
Section: Introductionmentioning
confidence: 83%
“…Until now, there is no effective vaccine for human use. These facts necessitate the continuous efforts to discover and develop novel nonantibiotic antichlamydial agents [16][17][18][19][20][21][22][23][24][25]. In search for antichlamydial agents from the synthesized compounds, we firstly reported that a group of pyrroloisoxazolidines inhibited C. trachomatis propagation.…”
Section: Discussionmentioning
confidence: 99%
“…However, no effective vaccine is available to prevent C. trachomatis infections up to date [13][14][15]. All these negative situations raise the pressing need to search for novel antichlamydial agents from natural materials or synthesized chemicals [16][17][18][19][20][21][22][23][24][25]. Isoxazolidine derivatives are a group of chemicals that possess a variety of biological and pharmaceutical activities including neuroactive, antioxidant, antibacterial, antifungal, and antiretroviral properties [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%